Comparison of Antibacterial Properties of Salvia Officinalis with Commercially Available Mouth-Rinse - Ambreen Khurshid Haider, Syeda Bisma Naseem, Zafar Iqbal, Faizan Ashar, Mah Zul Kaif, Muhammad Tariq Fayyaz (Pakistan Journal of Medical & Health Sciences, 2023)
Dental caries, commonly known as cavities/tooth decay, is a widespread and one of the most prevalent diseases affecting people of all ages. Despite its prevalence, dental caries is largely preventable through good oral hygiene practices and reducing sugar intake. A variety of commercially available mouthwashes are being recommended by dental health professionals because of their antibacterial properties but their side effects limits the use of these mouth washes hence, plant based natural compounds are being evaluated for their antibacterial properties in the current study Salvia Officinalis was evaluated in this regard. Methodology: It was an in-vivo preclinical experimental study conducted from October 2022 to January 2023. The calculated sample size was n =60The participants were given an envelope for group randomization. The organisms were grown on appropriate media and extract was prepared and diluted. The extract was diluted in distilled water at 1:4 (Extract: Distilled water) concentration. Study participants were instructed to not brush their teeth before sampling. Study participants were divided into three groups (negative control, positive control, Salvia Officinalis extract rinse group) each group had 20 participants. Diluted SO extract was given to the experimental group for rinses, distilled water was given to the negative control group and positive controls were given a standard commercially available mouth rinse. The next sample of plaque was collected after two hours to observe the effects of SO extract on bacterial colonies. Results: The pre and post-samples showed a significant (p-value <0.05) decrease in number of colonies in the positive control group (conventional rinse) and Salvia officinalis extract group. The intra-group comparison of negative and positive control showed a significant difference in number of colonies and the same was observed with the Salvia officinalis rinse. However, the positive control and Salvia officinalis extract comparison was insignificant. Conclusion: The invitro experiment highlighted that the S. officinalis plant extract has equivalent effects against S. mutans and P. gingivalis as that of commercially available mouth rinse. Keywords: Salvia officinalis, S. mutans, P. gingivalis, Moth rinse